Accumulation of heavy metals using Sorghum sp - Soudek, Petr; Petrová, Šarka; Vaňková, Radomíra; Song, Jing; Vaněk, Tomaš (Chemosphere, 2014)
The essential requirement for the effective phytoremediation is selection of a plant species which should be metal tolerant, with high biomass production and known agronomic techniques. The above mentioned criteria are met by crop plant sorghum (Sorghum bicolor). The response of hydroponically grown S. bicolor plants to cadmium and zinc stress was followed. The impact of metal application on physiological parameters, including changes in chlorophylls contents and antioxidative enzymes activities, was followed during the stress progression. Cadmium and zinc were accumulated primarily in the roots of sorghum plants. However, elevation of metal concentrations in the media promoted their transfer to the shoots. Toxic effects of metals applied at lower concentrations were less serious in the shoots in comparison with their influence to the roots. When applied at higher concentrations, transfer of the metals into the leaves increased, causing growth reduction and leading to Chl loss and metal-induced chlorosis. Moreover, higher metal levels in the roots overcame the quenching capacity of peroxidase and glutathione transferase, which was associated with reduction of their activities. Fortification of antioxidant system by addition of glutathione significantly increased the accumulation of cadmium in the roots as well as in the shoots at the highest cadmium concentration applied.
Keywords: Accumulation; Plant Leaves; Oxidative stress; biodegradace; Peroxidases; Zinc; zinek; Biodegradation, Environmental; listy rostlin; Sorghum; biomasa; Glutathione; Cadmium; kořeny rostlin; kadmium; glutathion; peroxidasy; Biomass; Plant Roots